KEPASTIAN HUKUM PENYERAHAN PROTOKOL NOTARIS KEPADA PENERIMA PROTOKOL - Sukma Cahyani, Ida Ayu Md Dwi; Usfunan, Yohanes; Sumardika, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan, 2017)
Notary Authority is very important for the parties who make an agreement under the civil law. In performing their duties, notaries are required to maintain their accuracy and prudence, in order to provide justice, without any discrimination, thus providing legal certainty and the protection of human rights of the parties concerned. Under the provisions of Article 63 of the Law on Notary, there has been obscurity and vacuum of norms. The said obscurity of norm is about the certainty of protocols’ submission of notaries which have been overdue as specified on the provisions of Article 63 of Law on Notary Position. The vacuum of norms also mean the lack of certainty about who is responsible for the notary protocols, the absence of the regulations related to who should receive the protocols and the lack of sanctions against the notary who has been designated to receive the protocol by the Regional Supervisor Assembly but was not willing to accept the protocol. These provisions give rise to legal issues namely: what  the legal consequences of Notary Protocols that have not been submitted after the deadline for submission and how the provisions of sanctions against the notary who is not willing to accept the protocols. The type of research used in this thesis was a normative legal research because of the obscurity and the vacuum of norms. The legal materials collection techniques used were a literature study and a card system. To analyze the legal materials, it was used descriptive techniques, interpretation, construction and argumentation theories and concepts associated with the relevant legal issues. The results showed that the Notary Protocol Submission to the recipient of the protocols which have passed the submission deadline resulted in some juridical consequences. The consequences include: Incidence of doubt, the uncertainty associated with the filing of the protocol the Notary. The lack of certainty associated with the accountability to the possibility of loss and destruction of the protocols of Notary. Other consequences that arise are if the parties concerned are unable to obtain a copy of their certificates back in the event of the onset of a dispute between the parties. If the notaries proved to have violated, they can be subject to sanctions. The sanctions that may be imposed on the Notaries if they make any violations are the administrative sanctions, civil penalties and criminal sanctions.